Assessing Preschool Children's Letter-Name Knowledge: Responsive Practices. (3rd July 2022) - Chen, Jennifer J.
Abstract: In this article, the author offers recommendations for pedagogical practice based on the assessment results of uppercase letter-name knowledge among Spanish-speaking preschool children from low-income backgrounds.